STRATEGI PEMBELAJARAN GURU DALAM PEMBINAAN KEPRIBADIAN SISWA - man, Herman man (Makassar Journal of Social Sciences, 2013)
This study aims to address (1) How learning strategies teachers of Junior High School social studies Somba Opu 2 Sungguminasa District of Gowa, (2) What personality development of students of SMP Negeri 2 Somba Opu Sungguminasa District of Gowa and (3) Is there a relationship strategy teachers of social studies lessons on personality development of students in Junior High School 2 Somba Opu Sungguminasa District of Gowa. The research used the quantitative descriptive statistical research. The population in this study were all students of SMP Negeri 2 Somba Opu Sungguminasa District of Gowa as many as 1268 students, then selected a sample through random sampling techniques to facilitate researchers and selected 91 students. Data collection techniques in this study by using observation, questionnaire, and documentation. The results of the questionnaire were then described by descriptive percentages. Based on the research results of teacher learning strategies in the excellent category, it is seen from 48 students from indikato - indicators of learning strategies (1) Preparation (Preparation), (2) Presentation (Presentation), (3) correlation (correlation), (4) Summing up (generalization), (5) Application (Application). Personality development of students are also considered kategor very good , it is seen from the 58 students of the indicators (1) conduct, (2) craft, (3) tidiness, (4) cleanliness . In addition there is a relationship between learning strategies teachers with personality development of students